ANALISIS KINERJA KEUANGAN KELOMPOK BANK BERDASARKAN MODAL INTI (KBMI) III DI INDONESIA PERIODE 2019 - 2021 - Tazkia Alfisyahri, (2023)
The COVID-19 pandemic that occurred in early 2020 made most offices and industries prohibited from operating for a relatively long period of time. This of course has an impact on economic losses in various fields and sectors in Indonesia. One of them is the banking sector which has an important and strategic role in driving the wheels of the national economy and supporting the implementation of national development. This can be seen from customers who keep their funds in the Bank, not only from individuals but also customers from large companies. Therefore, if the Bank's condition is unhealthy, it will have an impact on its customers. The phenomenon of the global crisis caused by the COVID-19 pandemic certainly had an impact on banking performance. This research shows that the Loan to Deposit Ratio (LDR) at Banks belonging to the Bank Group based on Core Capital (KBMI) III for the 2019 - 2021 period has decreased due to an increase in total third party funds collected by banks while the total loans distributed are more a little. This decrease in the LDR ratio affects the CAR ratio. Because the LDR ratio decreases, the CAR ratio increases. This is due to the reduced value of the risks that will be faced by banks in extending credit. Keywords: Core Capital, KBMI, Bank, COVID-19